Negligible contribution of body density to in-water vertical jump performance in elite male water polo players - Balázs, B.; Sebesi, B.; Cselkó, A.; Váczi, M. (PLOS ONE, 2024)
The aim of this study was to investigate the associations among in-water vertical jump and various dry-land physical measures by taking the law of Archimedes into consideration, and by normalizing the dry-land measures both to body density and body mass. Seventeen elite water polo players from Hungarian first league were tested for dry-land counter movement and squat jump mechanical impulse, isometric squat force, and in-water vertical jump height. Body density was estimated by anthropometric measurements. Body density alone did not influence in-water vertical jump height. Both the impulse of counter movement jump normalized to body mass (9.42±0.86 N·s/kg) and impulse of counter movement jump normalized to body density (773.92±109.68 N·s/kg/g/cm3) correlated with the in water vertical jump height (69.37±6.12 cm) (p=0.05), but the magnitudes of the correlation coefficients 0.49 vs. 0.50 were not statistically different (p = 0.480, z = 0.04). Neither the impulse of squat jump normalized to body mass (7.07±0.59 N·s/kg) nor impulse of squat jump normalized to body density (577.87±89.16 N·s/kg/g/cm3) correlated with the in water vertical jump height (both p>0.05). The correlation between the force of the maximum voluntary isometric contraction normalized to body density (1052.13±244.65 N/kg/g/cm3) and the in water vertical jump height only approached the level of significance (p = 0.077). We concluded that dry-land reactive strength determines the ability to jump out of water, but players` body density does not seem to contribute to jump height.